The Effect of The Use of Fish Flour as a Source of Protein in Complete Feeds on The Digestivenes of Fat, Crude Fiber and Nitrogen-Free Extract in Bali Cattle Fattened - Agustinus Mau Mori; Oktavianus Rafael Nahak; Paulus Klau Tahuk (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2022)
The research has been carried out for 3 months, starting from May 13 to August 13, 2021 in the experimental cage of the Faculty of Agriculture, University of Timor, while the analysis of digestibility of fat, crude fiber, and Extract Material Without Nitrogen (EMWN) at the Chemistry Laboratory of the Faculty of Animal Husbandry, University of Nusa Cendana. The purpose of this study was to determine the effect of using fish meal as a protein source in a complete feed on the digestibility of fat, crude fiber, and EMWN in fattened male bali cattle. The method used in this study was a completely randomized design (CRD) which consisted of 3 treatments and 5 replications so that there were 15 experimental units. The treatments were: T1= Natural grass 30% + Milled corn 42% + Rice bran 13% + Brand Pollard 11% + Fish meal 4%, T2= Natural grass 30% + Milled corn 42% + Rice bran 9% + Brand Pollard 11% + fish meal 8%, T3=. Natural grass 30% + Milled corn 42% + Rice bran 5% + Brand Pollard 11% + fish meal 12%. The variables tested included Fat Digestibility (%), Crude Fiber Digestibility (%) and EMWN Digestibility%. The results of analysis of variance showed that digestibility of crude fat and digestibility of crude fiber had a significant effect (P<0.05) and digestibility of EMWN had no significant effect (P>0.05) on the percentage of digestibility of fat produced T1: 19.06%; T2; 34.11%; T3: 69.31%, digestibility of crude fiber produced T1: 42.13%; T2: 29.02%; T3: 18.52% and the resulting EMWN T1: 65.01%; T2: 60.28%; T3: 62.31%. It can be concluded that the use of completed feed prepared with fish meal containing 12% protein increased the crude fat digestibility value but the crude fat digestibility was lower when compared to 4% fish meal and 8% in fattened bali cattle. Meanwhile, the digestibility of EMWN was not affected by the use of different levels of fish meal in complete feeds.